The importance of parental involvement in swimming lessons for person with disability - Prado Júnior, Milton Vieira do [UNESP]; Nabeiro, Marli [UNESP]; Veneziano, Tatiane [UNESP]; Leite, Ivan [UNESP]; Martins, Laís [UNESP]; Gomes, Kelly [UNESP]; Toloi, Gabriela Galucci [UNESP] (My University, 2013)
The Ecolological Theory of Human Development proposed by Urie Bronfenbrenner assumes that the activities and people involved in an evironment are essential to stimulate the aquisition of new abilities . Analyze the strategy of parent’s presence with their children in a swimming class for PWD during the teaching process. Also, verify the parent’s views on this experience and the participation of their child during practice. It is a qualitative and action-research. To collect data was utilized observation during to analyse the activities developed in a swimming class for PWD, on the presence of parents with their children. A semi-structured interview was used to analyse the perception parents after the experience of the classroom. Analysis of activities and the interview were based on the assumption of Bronfenbrenner (1996). It was found that 100% of the parents rated the positive experience of being with their children in the pool. We found that only 25% of parents reported that had entered the pool to play with their children. We emphasize that 75% had never entered in the water with their children, whether because of fear, lack of opportunity or not knowing how to swim. The proposal of parents’ participation in the swimming class with the PWD generated a favorable environment for development the activities. Parents identified the improvement, the potential and difficulties of PWD.
Keywords: Swimming class; Person with disability; The ecological theory of human development